PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN PERSISTENSI LABA TERHADAP KUALITAS LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Lalo, Annas; Emil, Emil (Jurnal Unicorn ADPERTISI, 2025)
The purpose of this study is to examine the influence of Institutional Ownership, Company Size and Profit Persistence on Profit Quality in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period. This study uses a quantitative research approach. The population in this study is all manufacturing industry companies in the Food and Beverage sector on the Indonesia Stock Exchange for the 2020-2022 period